Uji Aktivitas Antijamur Ekstrak Jamur Endofit dari Alga Chondrus sp. terhadap Candida albicans - Ni Kadek Ari Kristiani; Ariantari, Ni Putu (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2023)
Endophytic fungi are an important source for the discovery and development of new drug molecules, including antifungals. Endophytic fungi associated with algae are one of the potential microorganisms to be further studied for their antifungal activity. This study aims to isolate and identify the endophytic fungi isolated from the algae Chondrus sp., to screen the content of secondary metabolites produced by these endophytic fungal isolates, and to test the activity of the extracts obtained against Candida albicans. The research began with the isolation and purification of endophytic fungi, fermentation in rice media, and extraction with ethyl acetate. The ethyl acetate extract obtained was then partitioned between methanol-water and n-hexane. The methanol extract was screened for chemical content and antifungal activity against C. albicans. In this study, 3 isolates of endophytic fungi were obtained with the codes A5-1-1, A5-1-2, and A5-2-1. Phytochemical testing showed that all methanol extracts of endophytic fungi from the algae Chondrus sp. contain alkaloid compounds, extracts from isolates A5-1-2 and A5-2-1 contain triterpene compounds, and extract A5-1-2 contains polyphenol compounds. The antifungal test showed that the endophytic fungi methanol extract with code A5-1-2 showed the best antifungal activity compared to the other two fungi extracts against C. albicans (MIC 500 μg/mL) which was included in the weak category.